Contamination of CSF Culture: Serious Risk to Patient Safety. (October 2020) - Garg, Rahul
Abstract : Background: Acute bacterial meningitis is a medical emergency, and early initiation of appropriate therapy is important to improving outcomes. Culture-based methods are still the standards for the detection of microorganisms in cerebrospinal fluid (CSF). Automated blood culture systems yield better results in cultures sterile body fluids, including CSF. However, the high sensitivity of this technology does not negate the danger of contamination compromising the final outcome. Thus, we tried to study the culture yield in suspected meningitis to determine the rate of contamination. Methods: We conducted a retrospective cohort study of CSF samples collected for culture over 1 year from January 2018 to December 2018 from patients who presented with signs and symptoms indicative of meningitis. The bacterial etiologies and rates of contamination were extracted from laboratory records. Descriptive statistics from Microsoft Excel software were used to analyze patient data. Limited statistical analysis (ie, the Fisher exact test) was performed using SPSS for Windows version 18 software. Results: In total, 1, 053 CSF samples were received for aerobic culture, of which the most frequent were conventional cultures (685 of 1053, 65%), whereas BacT/ALERT cultures were requested for 368 of 1, 053 cases (35%). Of 685 conventional CSF cultures, pathogens were isolated in 28 of 685 (4.1%), most commonly Acinetobacter baumannii complex (10 of 28, 35.7%). Contaminants were identified in 0.58% samples (4 of 685). In the 368 BacT/ALERT cultures, pathogens were detected in 15 (4.1%), most commonly Streptococcus spp (5 of 15, 33.3%). The contamination rate was 51.1% (188 of 368 cases). The overall rate of contamination was 18.2% (192 of 1, 053 cases). The most CSF cultures were received from patients in neurosurgery (350 of 1, 053, 33.2%) followed by medicine wards (270 of 1, 053, 25.6%). Aerobic spore bacilli was by far the most common contaminant (109 of 1, 053, 10.35%). Conclusions: We believe efforts to decrease contamination are among the most cost-effective, but targeted clinical re-evaluation for all patients with positive CSF cultures remains vital. Due to the high sensitivity of the automated culture system, it is a imperative to maintain strict aseptic conditions while collecting CSF samples. Failure to do so may lead to overgrowth of contaminants masking the growth of the true pathogens in culture. Disclosures: None Funding: None